The systematic approach to creating the proper motivation of young researchers in scientific institutions - Alekseevna Romanovich, Marina; Safaie, Nasser; Agha Kazem Shirazi, Samaneh (Serbian Journal of Management, 2023)
The study aimed to find out how to develop an optimal and effective motivation model considering the preferences and requests of young researchers, in view of the fact that scientific specific of building and organising an internal work system, its scientific potential and resources, which provides a valuable fundamental insight. The task of the study was to develop and propose a mechanism that would be specially adapted for scientific institutions and universities. That was based on an in-depth analysis of the existing approaches of scientists regarding the specifics of the work of these organisations. The developed method is relevant to modern literature, where the definition of a motivational approach eliminates the dichotomy between existing studies. The data were collected by interviewing responders from Russian and Iranian universities. The study results show the subjective aspects of the perception of research activities by students and researchers and the shortcomings in constructing motivation systems. As a result of implementing the proposed optimal and effective "Model of proper motivation system", scientific institutions can strengthen their positions and establish sustainable activities to attract talented scientists and innovators to develop scientific progress and compete in the market knowledge-intensive services.
Keywords: motivation; scientists; scientific institutions; cluster analysis